Analisa Karakteristik Daerah Untuk Menentukan Strategi Penagihan Rekening Listrik Konsumen PT PLN (Persero) Yang Efektif dan Efisien Dengan Metode AHP (Analytical Hierarchy Process) - Rahmada Mulia Whardana Moljoadie; Adi Saputro (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Like companies that are oriented to the buying and selling business in general, PT PLN (Persero) or PLN also has the same business risk, namely the existence of arrears on account receivables arising from electricity buying and selling transactions with consumers. These arrears cannot be avoided because PLN consumers have different characteristics, one of which is the economic factor of the consumers themselves. In addition, because of force majeure is also one of the causes of arrears in electricity buying and selling transactions, including natural disasters and other calamities. By getting cash in from electricity bills collection, PLN's operations will of course be maintained so that service to customers can be even better. However, it is necessary to carry out an analysis related to the billing mechanism used using external factors to determine customer characteristics based on regional conditions. One method that is relevant and has a consistency value calculation in determining the priority level of criteria is the Analytical Hierarchy Process (AHP) method. The expected results of this study are a system that can provide recommendations for alternative billing strategies based on characteristics per region so that the hierarchy formed is acceptable for decision making.